A tritrophic analysis of host preference and performance in a polyphagous leafminer - Videla, Martin (2006)
The optimal oviposition theory predicts that oviposition preferences of phytophagous insects should correlate with host suitability for their offspring. As plant host suitability depends not only on its quality as food, but also on its provision of enemy-free space, we examined the relationship between adult host preference and offspring performance for the leafminer Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae) on various host plants, considering also the interaction with natural enemies. Preference and offspring performance were assessed through observational ﬁeld data and laboratory experiments in central Argentina. Field data suggested a positive host preference ? performance link- age, as the leafminer attained larger body size on the crops where it was more abundant. Laboratory trials supported these results: Vicia faba L. (Fabaceae) was the preferred host in the laboratory as well as in the ﬁeld, performance of L. huidobrensis being also best on this host, with highest survival rates and shortest development time. The actively feeding larval stage showed the largest plant-related effects. Higher overall parasitism rates were found on plants from which smaller leafminers were reared, reinforcing the preference?performance linkage. On the other hand, the main parasitoid phaedrotoma scabriventris Nixon (Hymenoptera: Braconidae) reached larger body size, and caused higher mortality rates on crops where the leafminer was larger. Changes in abundance of particular parasitoid species could thus modify overall parasitism trends.